Carriage of Class 1 and 2 Integrons in Quinolone, Extended-Spectrum-β-Lactamase-Producing and Multi Drug Resistant E.coli and K.pneumoniae: High Burden of Antibiotic Resistance - Froogh Shams; Alka Hasani; Mohammad Ahangarzadeh Rezaee; Mohammad Reza Nahaie; Akbar Hasani; Mohammad Hossein Soroush Bar Haghi; Ali Pormohammad; Asghar Elli Arbatan (Tabriz University of Medical Sciences, 2015)
Purpose: The study aimed at assessing any association between quinolone resistance, MDR and ESBL production and their relation with the presence of integrons in Esherichia coli and Klebsiella pneumoniae. Methods: E.coli and K.pneumoniae isolated from various clinical infections were fully identified and analyzed for being quinolone resistant. These isolates were further tested for ESBL production, multi drug resistance and carriage of integrons. Results: In total, 135 isolates were confirmed as quinolone resistant. K.pneumoniae was observed as potent ESBL producer in comparison to E.coli. Ciprofloxacin resistance in both organisms was related significantly with the presence of integron class 1, co-presence of class 1 and 2 as well as to the presence of ESBL production (p< 0.001). However, nalidixic acid resistance was related significantly (p< 0.01) with only integron class 1 and to the presence of ESBL production. Class 1 and 2 integrons were found in 73.5% of MDR isolates with 13.2% of them possessing both intI1 and intI2 genes. Conclusion: Prevalence of quinolone resistance together with ESBL production and MDR in E.coli and K.pneumoniae has contributed to the emergence of antibacterial resistance burden. The higher integron prevalence in our isolates advocates the potentiality of these isolates as a source for dissemination of resistance determinants.